2005
DOI: 10.1103/physrevlett.94.143903
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Resolution in the Focal Plane of an Optical Microscope

Abstract: Utilizing single fluorescent molecules as probes, we prove the ability of a far-field microscope to attain spatial resolution down to 16 nm in the focal plane, corresponding to about 1/50 of the employed wavelength. The optical bandwidth expansion by nearly an order of magnitude is realized by a saturated depletion through stimulated emission of the molecular fluorescent state. We demonstrate that en route to the molecular scale, the resolving power increases with the square root of the saturation level, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
340
0
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 453 publications
(350 citation statements)
references
References 13 publications
(16 reference statements)
2
340
0
8
Order By: Relevance
“…We simply write the conversion rate as c&aI 2 (see details in Supplementary Information), where I is the power of laser. The simplest function to depict the detection pointspread-function and the doughnut conversion laser intensity is the standing wavefunction: 38,39 h det r ð Þ~Ccos 2 pr=v det ð Þ ð 4Þ…”
Section: Csd Microscopymentioning
confidence: 99%
“…We simply write the conversion rate as c&aI 2 (see details in Supplementary Information), where I is the power of laser. The simplest function to depict the detection pointspread-function and the doughnut conversion laser intensity is the standing wavefunction: 38,39 h det r ð Þ~Ccos 2 pr=v det ð Þ ð 4Þ…”
Section: Csd Microscopymentioning
confidence: 99%
“…The development of stimulated emission depletion (STED) fluorescence microscopy [1][2][3], that took place at the turn of this century, demonstrated that the limiting role of diffraction can be overcome and nanosized features discerned with freely propagating light and conventional lenses. The decisive difference between STED and the traditional microscopy approaches is that the traditional ones discern the tiny features in the sample by the phenomenon of focusing.…”
Section: Introductionmentioning
confidence: 99%
“…Microscopy: The principles of STED microscopy have been described in detail elsewhere [6,[28][29][30]. In brief, as in conventional laser scanning microscopy, in STED microscopy fluorescent markers are typically excited by a focused laser, which is scanned across the sample.…”
Section: Methodsmentioning
confidence: 99%
“…If a molecule gets excited it is instantly pushed back to the ground state by stimulated emission effected by the STED beam. With increasing intensity of the STED beam, the area wherein the fluorophores are not turned off shrinks in principle to the size of a molecule [28,31]. With the STED beam blocked, the microscope simply operates as a standard confocal laser scanning microscope.…”
Section: Methodsmentioning
confidence: 99%